2021
DOI: 10.1136/postgradmedj-2021-140674
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension as an independent risk factor for severity and mortality in patients with COVID-19: a retrospective study

Abstract: Purpose of the studyHypertension is one of the most common comorbidities in COVID-19 pneumonia. However, whether it is an independent factor on the severity and mortality of COVID-19 has not been studied.Study designIn this study, 736 patients with a PCR-confirmed diagnosis of COVID-19 were included from 12 January 2020 to 25 March 2020. All patients were divided into two groups according to whether or not they were hypertensive. After propensity score matching (PSM) to remove the interference of mismatches in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…However, the two factors with the greatest association with the development of a HAPI in COVID-19 patients were diabetes mellitus and arterial hypertension. This association may be due to the established relationship between increased rates of hospital admission, severity and mortality of COVID-19 in patients with these comorbidities [ 16 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the two factors with the greatest association with the development of a HAPI in COVID-19 patients were diabetes mellitus and arterial hypertension. This association may be due to the established relationship between increased rates of hospital admission, severity and mortality of COVID-19 in patients with these comorbidities [ 16 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the odds of death were five times higher among diabetic patients with hypertension comorbidity than those without hypertension [(AOR= 5.01; 95% CI: 2.40, 10.60), p<0.001]. Former studies conducted in China and Nigeria also showed the association of hypertension with increased mortality of COVID-19 patients (30-33). The exact pathologic link between hypertension and COVID-19 is unclear yet.…”
Section: Discussionmentioning
confidence: 97%
“…Former studies conducted in China and Nigeria also showed the association of hypertension with increased mortality of COVID-19 patients (30)(31)(32)(33). The exact pathologic link between hypertension and COVID-19 is unclear yet.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%
“…Stress, as a risk factor causing hypertension, particularly in the case of white coat hypertension (WCHT), is a threat to increase the severity of COVID-19. 1 , 2 , 3 Therefore, this brief letter focuses on WCHT.…”
mentioning
confidence: 99%
“…In this respect, managing WCHT can be prioritized to avoid severe COVID-19 and cardiovascular events. 2 , 4 …”
mentioning
confidence: 99%